Early Immune Regulatory Changes in a Primary Controlled Human Plasmodium vivax Infection: CD1c + Myeloid Dendritic Cell Maturation Arrest, Induction of the Kynurenine Pathway, and Regulatory T Cell Activation - Yeo, Tsin Wen (2017)
Plasmodium vivax malaria remains a major public health problem. The requirements for acquisition of protective immunity to the species are not clear. Dendritic cells (DC) are essential for immune cell priming but also perform immune regulatory functions, along with regulatory T cells (Treg). An important function of DC involves activation of the kynurenine pathway via indoleamine 2,3-dioxygenase (IDO). Using a controlled human experimental infection study with blood-stage P. vivax, we characterized plasmacytoid DC (pDC) and myeloid DC (mDC) subset maturation, CD4+ CD25+ CD127lo Treg activation, and IDO activity. Blood samples were collected from six healthy adults preinoculation, at peak parasitemia (day 14; ∼31,400 parasites/ml), and 24 and 48 h after antimalarial treatment. CD1c+ and CD141+ mDC and pDC numbers markedly declined at peak parasitemia, while CD16+ mDC numbers appeared less affected. HLA-DR expression was selectively reduced on CD1c+ mDC, increased on CD16+ mDC, and was unaltered on pDC. Plasma IFN-γ increased significantly and was correlated with an increased kynurenine/tryptophan (KT) ratio, a measure of IDO activity. At peak parasitemia, Treg presented an activated CD4+ CD25+ CD127lo CD45RA− phenotype and upregulated TNFR2 expression. In a mixed-effects model, the KT ratio was positively associated with an increase in activated Treg. Our data demonstrate that a primary P. vivax infection exerts immune modulatory effects by impairing HLA-DR expression on CD1c+ mDC while activating CD16+ mDC. Induction of the kynurenine pathway and increased Treg activation, together with skewed mDC maturation, suggest P. vivax promotes an immunosuppressive environment, likely impairing the development of a protective host immune response.